Thermally altered marine dissolved organic matter in hydrothermal fluids - Rossel, Pamela E.; Stubbins, Aron; Rebling, Tammo; Koschinsky, Andrea; Hawkes, Jeffrey A.; Dittmar, Thorsten (Organic geochemistry, 2017)
•DOM composition was influenced by fluid contribution and thermal decomposition.•Thermally altered DOM had low molecular weight, and was oxygen poor and more aromatic.•Hydrothermal fluid DOM was molecularly similar to thermally altered marine DOM.•Carboxyl-rich alicyclic formulae were removed after thermal decomposition. Hydrothermal vent fluids contain thermally modified dissolved organic matter (DOM) originally entrained from sediments and seawater. We hypothesized that in hydrothermal systems DOM molecular composition is modulated by (i) fluid contribution, (ii) thermal decomposition and pH, and (iii) aspects particular to the vent system. Hence, solid phase extracted (SPE) DOM samples collected along the Mid-Atlantic Ridge (MAR) were molecularly characterized via 15 Tesla Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). The molecular character of an oceanic DOM sample was also determined before and after thermal (300°C) decomposition at acidic and neutral pH. Multivariate statistical analysis indicated that DOM composition was strongly influenced by fluid contribution (Mg2+ concentration between 12 and 54mM), which correlated positively with measured temperature (between 8 and 375°C). In comparison, pH of the fluids (between 2.5 and 6.9) had a minor influence. Seafloor pressure, used as a theoretical maximum fluid temperature at the seafloor, separated the fluids collected at Menez Gwen from deeper locations, due to the higher abundance of peptide, carboxyl-rich alicyclic (CRAM) and aromatic molecular formulae at Menez Gwen. Compared with seawater DOM, thermally decomposed DOM had on average lower molecular mass, lower O/C ratios, fewer double bond equivalents, and fewer CRAM formulae but higher aromaticity - the same molecular features displayed by MAR hydrothermal fluids. The study provides evidence that thermal reworking plays a major role in shaping DOM mixtures from hydrothermal fluids along the MAR, which partly represent thermally reworked marine DOM that survived hydrothermal circulation.